Language Society and Social Interaction: Language Choice of Arabic Society at Imam Bonjol Islamic State University - Rahmat Satria Dinata (Fakultas Tarbiyah Program Studi Pendidikan Bahasa Arab Institut Agama Islam Darullughah Wadda'wah Pasuruan, 2021)
Abstract The term language society emerged and was developed from the term issued by Fishman (1976) about speech community. In relation to the term language society, this study aims to determine the choice of language among the Arabic language society at Imam Bonjol State Islamic University, Padang, and their attitudes towards their environmental language (Arabic), regional language ​​(Minang), national language ​​(Bahasa). This research is a descriptive study that describes the choice of language by a language society. The results of the study show that: Firstly, the students or the Arabic language society at Imam Bonjol State Islamic University Padang sometimes use Arabic and Minang language in class, but frequently use Bahasa in class. Secondly, the students or the Arabic language society very rarely use Arabic outside the classroom, often using Minang and Bahasa outside the classroom. Thirdly, the students often do code-mixing or code-switching between Arabic, Bahasa, and Minang languages. Keywords: Arabic; Bahasa; Minang; Mutilingual; Society